2016
DOI: 10.7324/japs.2016.60209
|View full text |Cite
|
Sign up to set email alerts
|

Validated, Ultra High Efficiency RP-HPLC and Stability Indicating Method for Determination of Tranylcypromines Sulphate in Bulk and in Tablet Dosage Forms

Abstract: Simple, sensitive, rapid and stability indicating ultra high efficiency RP-HPLC method was developed and validated for analysis of Tranylcypromine sulphate in bulk drug and in tablet dosage forms. Well-resolved peaks of target analyte and its degradation products were achieved on a Kinetex ® column (75 mm x 4.6 mm ID) 2.6 µm at 30 °C , using simple isocratic mobile phase of acetonitrile -orthophosphoric acid 0.1 % (10: 90, v/v). The flow rate was 1.0 mL/min and the detection was performed at 220 nm. The retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…12 Ragab et al noted that tranylcypromine is relatively stable on exposure to ultraviolet light and that only small amounts of degradation products can be detected using reversed-phase HPLC; the authors concluded that the cyclopropyl ring opens in both acidic and alkaline conditions and that the degradation products have different chemical structures from amphetamine and methamphetamine. 17 One possible explanation for the discrepancies in the findings of the aforementioned studies may be individual variations in drug metabolism among patients. For example, ethnic variations in cytochrome P450 isoenzymes have resulted in differing levels of metabolic activity, clinical responses and drug interactions.…”
Section: Resultsmentioning
confidence: 75%
“…12 Ragab et al noted that tranylcypromine is relatively stable on exposure to ultraviolet light and that only small amounts of degradation products can be detected using reversed-phase HPLC; the authors concluded that the cyclopropyl ring opens in both acidic and alkaline conditions and that the degradation products have different chemical structures from amphetamine and methamphetamine. 17 One possible explanation for the discrepancies in the findings of the aforementioned studies may be individual variations in drug metabolism among patients. For example, ethnic variations in cytochrome P450 isoenzymes have resulted in differing levels of metabolic activity, clinical responses and drug interactions.…”
Section: Resultsmentioning
confidence: 75%
“…The chromatographic analysis was carried out according to the reported method [19]. Chromatographic condition is based on isocratic elution mode at ambient temperature.…”
Section: Chromatographic Instrument and Conditionsmentioning
confidence: 99%